An analysis of Australian mutual fund performance and market relationships - Pojanavatee, Sasipa (Curtin University, 2013)
Mutual funds are emerging as an opportunity for investors to automatically diversify their investments in such a way that all their money is pooled and the investment decisions are left to a professional manager. There are various types of mutual funds that generally come with different investment objectives. Consequently, mutual funds have grown to play an important role in financial markets and the price prediction evaluation of mutual funds have performed has evolved into an important topic for investors and academicians consider over the last decade.Portfolio theory demonstrates that the gains from a diversified portfolio involve different degrees of price co-movement between securities. If domestic equity markets have a long-run tendency to diverge from equilibrium, there are gains to be made from domestic diversification between equity mutual funds and the stock market. According to the rational expectations and the efficient market hypothesis, the expectations of future prices are equal to optimal forecasts using all currently available information. If equilibrium does exist then the market signals would function properly. The implications for rational expectations are that most of the information gleaned from market prices will be known. Then, if the prices of equity mutual funds and stock markets tend to converge, this suggests that the price of one security can be used to predict another.Understanding the price behaviour and performance of mutual funds would be useful for investors who have a choice of investment. Knowledge of the causes and degree of equity mutual fund volatility is beneficial to policy makers and economic forecasters in predicting the direction of mutual fund prices. However, previous Australian studies have only been limited into testing explicitly of superannuation funds and wholesale funds. These results have lead to a number of interesting and important research questions.The preliminary objective of this thesis is evaluating the performance of equity mutual funds. It provides guidance to the investors on how they can use performance analysis at the time of investment decision making. The risk adjusted performance of equity mutual funds has been measured through traditional measures such as Sharpe and Treynor ratios, and Jensen’s alpha performance measures. The autoregressive conditional heteroskedasticity and generalized autoregressive conditional heteroskedasticity models are constructed to provide information of equity mutual fund return volatility clustering.The primary objective of this thesis is to examine the lagged relationship between equity mutual funds and the stock market. The interesting finding in this study relates to the degree to which equity mutual fund prices influence stock market prices and to what extent security prices drive mutual fund prices. Therefore, potential price relationships may also exist between the different equity mutual fund categories. This study has important implications for both the stability and the forecasting of stock prices and returns.There is a need to understand the effects of lagged security prices on equity mutual fund prices through its influence on the stock market and vice versa. The main objective of the research, then, is to investigate the price volatility of the stock market and equity mutual funds by estimating vector auto-regression and vector error correction models to uncover the transmission mechanisms of the specified variables. Long-run price co-movements are detected by employing Johansen cointegration tests, and the short-run price dynamic is analysed by the Granger causality/Block Exogeneity Wald test with variance decompositions and impulse response function and an examination of error correction terms to investigate the speed of the models to reach equilibrium and thus long-term exogeneity.ivAnalysis of Australian equity mutual funds is not only important for investors and fund managers, but also for academics and policy makers, in examining the implications of investing in domestic equity markets. In this study, the existence and possible causes of the price dynamics are investigated over the period from 2000 to 2010 using daily data. Three study periods are considered, namely the period before the global financial crisis in 2007, the period after it, and the full period. Therefore, the study provides a further examination of mutual fund performance and price linkages by controlling for various equity mutual fund categories that can be useful to investors on which segments of Australian equity mutual funds they should consider investing in for differing economic conditions. The study also offers guidance to investors on which segments of Australian equity mutual fund prices are related to stock market prices and how they can use analysis of the prediction of market prices at the time of investment decision making.A number of Australian studies have focused on superannuation funds and unit trusts used monthly, annual data and replicate the data over a short-term study period. This dissertation focuses on open-ended equity mutual funds with a long study period using daily data. In many studies, the price linkages in long-run equilibrium estimated using Engle-Granger cointegration and Granger-causality tests are used to measure the short-run price linkages. This study investigates the price relationship between equity mutual funds and the stock market by controlling equity mutual fund categories using a time-series vector error correction model approach including stationarity tests, cointegration tests and Granger-causality and Block exogeneity tests to capture the security price volatility in both short-run and long-run relationships. Therefore, impulse response functions and variance decompositions are generated to explain the response to the price shock between the stock market and equity mutual funds. The unification of various estimation dynamic models of pricing provides a sufficient evidence to support (reject) the hypothesis of this study.Most of the previous studies test uni-directional causality and only a small number of studies take structural breaks into account. Unlike previous studies, this study provides an analysis of two-way causality between the specified variables and considers tests for dynamic pricing with allowance for structural breaks. This study therefore contributes further with its investigation of the price dynamics in the equity mutual funds, which have not been previously addressed.The Sharpe, Treynor and Jensen’s alpha performance measure results have documented negative performance, indicating that equity mutual fund is below as compared to market portfolio performance over the three study periods. The probable reasons that can be made performance diverge between market portfolio and equity mutual funds are management fees, taxation and timing effects. Risk adjusted performance results of equity mutual funds depict negative risk adjusted returns to investors. The autoregressive conditional heteroskedasticity and generalized autoregressive conditional heteroskedasticity results suggest that the volatility in equity mutual fund returns exhibits a persistence of volatility and mean reverting behaviour, especially for middle and small-cap equity mutual funds. This indicates that historical volatility does add considerable explanatory power to forecasts based on implied volatilities. Therefore, there is evidence of structural shifts in volatility during the post-crisis period. The cause of volatility may be a result of new unanticipated information and trading volume changes that create the change in the expected returns for equity mutual funds.Returning to the lagged models, the results indicate that the long-run pricing of equity mutual funds are cointegrated with the stock market index during the three study periods. In the short-run, the results indicate that some equity mutual fund categories possess both long-run and short-run exogeneity with the stock market. Therefore, the short-run dynamic indicates short-run Granger causal links running between different equity mutual fund vicategories. A multivariate vector error correction model, variance decomposition and impulse response function analyses, add further evidence that the stock market index is lower strongly exogenous, indicating that changes in equity mutual fund prices are passed on to stock market index prices so as to maintain an equilibrium.Thus, there are no existing potential long-run domestic portfolio diversification gains for investors in the sense that there is evidence of a cointegrating of the relationship between equity mutual funds and the stock market index according to portfolio theory. However, the equity mutual funds may offer gains for investors seeking to replicate the movement in the stock market. Based on the rational expectations and the efficient market hypothesis, the expectations of future prices are using the knowledge of the past price behaviour in particular the equity mutual fund category to improve forecasts of prices of other equity mutual fund categories and the stock market index. These results provide more useful guidance in drawing definitive conclusions regarding the rational expectations hypothesis.The study recommends that the future research should attempt to use panel data and cover a longer study period based on mutual fund holdings. It is important to understand the impact of equity mutual fund holdings on equity mutual fund prices. This will provide valuable knowledge on the extent to which particular shares drive the equity mutual fund prices and lead to understanding more about price interaction between equity mutual funds and the stock market based on the style of diversification.